The Impact of Fiscal Stimulus on Agriculture Sector in Bali: Interregional Input-Output Analysis - I Gede Agus Ariutama; Acwin Hendra Saputra; Muhammad Abdul Muis; Adi Nugroho (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2022)
This study aims to estimate the economic impact of 2021 fiscal stimulus on agriculture, forestry and fishing sector in Bali at national and regional levels. This study utilizes secondary data from Bali Province Regional Fiscal Review year 2021 from Regional Office of Directorate General of State Treasury of Bali Province and statistical data from the Central Statistics Agency. The interregional input-output (IRIO) model is employed to determine the value of the economic impact on 17 business sectors in 34 provinces in Indonesia. This study found that the fiscal stimulus on the agriculture sector has a positive impact on Bali economy resulting in two and a half times greater than the direct impact. Furthermore, the sector with the largest total impact was the construction sector, mining and quarrying sector and agriculture, forestry and fishing sector in Bali. In addition, the fiscal stimuli on the agriculture sector resulted in a significant economic growth impact not only in Bali as the region receiving the stimuli, but also in the neighboring regions. The implications of this research are related to stimulus allocation on the certain sector when the negative shocks occurred such as covid-19 pandemic, which can be used as input for evaluating government spending policies. In general, it can be concluded that the Government of Indonesia was successful in carrying out fiscal stimuli since they produced an economic impact greater than the allocated incentives.